Avaliação de risco e retorno em fundos de investimento multimercado e de previdência - Venudo, Tatiane de Sá (2024)
This paper focuses on the analysis of multimarket and pension investment funds, with an emphasis on the evaluation of risk and return using the Sharpe Ratio and Value at Risk (VaR), demonstrating how these measures can provide a clearer perception of each asset. This enables managers to determine which assets should be maintained in the investment fund portfolio and allows stakeholders to better assess their investments. The main objective of this study is to demonstrate the importance of financial tools for risk and return analysis, particularly the Sharpe Ratio and VaR, in multimarket and pension investment funds. While the Sharpe Ratio is used to measure risk-adjusted returns, assessing how efficiently a fund generates additional returns for the risk taken, VaR is a statistical measure that quantifies the maximum potential loss a fund can suffer over a specified time horizon, given a certain confidence level in the analysis. The study’s methodology involves the collection and analysis of historical data from multimarket and pension investment funds, followed by the calculation of the Sharpe Ratio and VaR for each fund. The analysis aims to demonstrate the effectiveness of these two measures in evaluating risk and return, highlighting the advantages and limitations of each. The results of the analysis seek to provide a deeper understanding of how the Sharpe Ratio and VaR can be used together to offer a more comprehensive evaluation of the performance of multimarket and pension investment funds. While the Sharpe Ratio is useful for identifying funds that offer the best risk-adjusted return, VaR provides insight into the risk of extreme losses. By combining these two tools, a more robust approach to the selection and management of multimarket and pension investment funds can be achieved